Investigation of Irrational Beliefs According to Some Variables in Adults - Demir, Yasin; Kumcagiz, Hatice (My University, 2019)
Irrational beliefs affect individuals' emotions and behaviors from the first stages of their lives and this effect continues throughout their lives. The aim of this study was to investigate irrational beliefs in adults in terms of various variables. This study is a descriptive study performed in survey design. . The study working group is consisted of the adults living in Samsun, Turkey. In the study, it was concluded that irrational beliefs do not differentiate significantly according to gender. This study was reached, 235 adult individuals aged between 27 and 50. 132 (56.17%) participants were female and 103 (43.83%) were male. The irrational beliefs of the participants were examined according to gender, age and education level. The data were collected by the Rational Beliefs Scale and personal information form. SPSS package program was used for data analysis. Data were analyzed by t test, ANOVA and Pearson Correlation Analysis. According to study, there is a significant difference in the irrational beliefs of the adults according to their education level, and the irrational belief levels of the secondary and high school graduates has been found to be significantly higher than the individuals who received undergraduate and higher education. In the literature, similar studies with the same results has been come across and as well as non-similar studies. It is recommended that qualitative studies including in-depth interviews should be conducted in order to determine exactly which factors are affecting irrational beliefs the most.
Keywords: Psikoloji; Davranış Bilimleri